2019
DOI: 10.3390/fib7080069
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of PA66/GO/MWNTs-COOH Nanocomposites and Their Fibers

Abstract: Good dispersion and interfacial compatibility are the key issues to realize the full potential of the physical–mechanical properties of nanocarbon-materials reinforced composites. Styrene–maleic-anhydride-copolymer (SMA)-treated graphene oxide (GO), carboxylated multiwalled carbon nanotubes (MWNTs-COOH), and solid-state shear milling (S3M) were applied to further improve the physical–mechanical properties of the nanocomposite fibers. The results show that a mixture of GO/MWNTs-COOH exhibits good dispersion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Previous reports showed that the effect of the synergistic reinforcement was the most effective when GO and MWCNTs were mixed at a mass ratio of 2:3. [ 45,46 ] Taking the TLCP/GO‐MA/MWCNTs‐NH 2 mixture as an example, the GO‐MA and MWCNTs‐NH 2 with a mass ratio of 2:3 were ground in a planetary ball‐mill at a constant rotational rate of 100 rpm for 15 min. The GO‐MA/MWCNTs‐NH 2 mixture and the dried TLCP were then added to the high‐speed kitchen blender (1000 W, 50 Hz) equipped with a four‐pointed star‐shaped blade.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports showed that the effect of the synergistic reinforcement was the most effective when GO and MWCNTs were mixed at a mass ratio of 2:3. [ 45,46 ] Taking the TLCP/GO‐MA/MWCNTs‐NH 2 mixture as an example, the GO‐MA and MWCNTs‐NH 2 with a mass ratio of 2:3 were ground in a planetary ball‐mill at a constant rotational rate of 100 rpm for 15 min. The GO‐MA/MWCNTs‐NH 2 mixture and the dried TLCP were then added to the high‐speed kitchen blender (1000 W, 50 Hz) equipped with a four‐pointed star‐shaped blade.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, in order to design composites for antifrictional purposes, other fibrous fillers are also actively used, among which the important role belongs to organic fibers (OF) [10,11]. The expediency of using different OF for reinforcing polyamides is confirmed by the improved tribotechnical and thermophysical characteristics [12,13].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The incorporation of micro and nanoscale additives into PAs to increase the mechanical properties while maintaining the overall weight became an important research subject. [15][16][17] Mainly; SiO 2, 18 clay, 19 calcium carbonate, 20,21 and carbonaceous materials such as carbon nanotubes, 22,23 carbon fiber (CF), 24 carbon black (CB), 25 exfoliated graphite, 26 and lately graphene 27 and graphenerelated materials 28,29 are being used to enhance the mechanical properties of polymers while maintaining the desired weight. Nevertheless, several challenges remain for the incorporation of such small-scale additives into the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%